Comparison of the efficiency of combined extracorporeal shock-wave therapy and triple therapy versus triple therapy itself in Category III B chronic pelvic pain syndrome (CPPS). (2nd July 2016) - Pajovic, B.; Radojevic, N.; Dimitrovski, A.; Vukovic, M.
Abstract: The aim of this study is to determine the effect of combining extracorporeal shock-wave therapy (ESWT) and triple therapy versus triple therapy alone, when treating Category III B chronic prostatitis (CPPS). Study included 60 patients, classified as having CPPS, divided into two groups: the first group numbered 30 patients, who were treated with a combination of an α-blocker, an anti-inflammatory agent and a muscle relaxant; the second group consisted of 30 patients who received a combination of ESWT and the fore-mentioned triple therapy. Patients were treated for 12 weeks. The primary criterion of a response to therapy was scoring 2 or less on the NIH-CPSI quality of life item, while the secondary criterion of a response to therapy was a greater than a 50% reduction in NIH-CPSI pain score. Patients who received triple therapy did not show a significant change neither in post void residual urine (PVR) nor in maximum flow rate ( Q MAX ), while the second group of patients exhibited significant improvement in both PVR and Q MAX values. Both groups of patients showed statistically significant improvement in all items of the NIH-CPSI score after the treatment, with significantly better results in the second group.